Possibility of Using Active and Passive Bank Products in Order to Maximize a Retail Customer’s Benefits (Economic and Political Thought, 2010)
The article aims at presenting benefits and advantages of bank productsavailable to a retail customer.The author attempts to prove that the recent two years of the economiccrisis, which was a result of financial institutions employees’ misappropriation,also resulted in the lack of customers’ openness to innovative financialproducts. A positive aspect of the whole situation is a closer and closer perspectiveof the end of the crisis and some hope that bad experiences will betransformed into greater caution and interest in acquiring knowledge.The article was based on the commonly available domestic literaturedealing with the issue of banking in Poland and two foreign sources on investment.It turned out that another important aspect was the use of Internetresources and the author’s practical expertise which enabled the presentationof the newest trends in the Polish banking system.